OPTIMALISASI PERAN DAN FUNGSI KEPANITERAAN DALAM MENDUKUNG ADMINISTRASI PENGADILAN - Yudy Setiawan; Muhammad Rezki; Ahmad Shirotol; Ali ambar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The justice system has a crucial role in law enforcement, where the clerkship is one of the important elements that ensures the smooth administration of the courts. However, in practice, clerkships often face various challenges, such as limited human resources, complex bureaucratic procedures, and uneven technology adoption. This research uses documentation, interviews and literature study methods to obtain relevant data regarding the implementation of clerkship duties. The research results show that optimization of clerkships can be done through increasing human resource competency, utilizing information technology such as e-Court, as well as reforming administrative procedures to increase efficiency and transparency in case management. This internship provides direct insight into how court administration works and the challenges faced in practice. It is hoped that the findings in this report can provide input for relevant agencies in improving the effectiveness of clerkships to support better justice services for the community.